Driver visual behavior while using adaptive cruise control on commercial motor vehicles. (January 2019) - Grove, Kevin; Soccolich, Susan; Engström, Johan; Hanowski, Richard
Highlights: We sampled data from 147 drivers across 132 commercial trucks equipped with ACC. We calculated visual metrics for combinations of ACC status and car following status. Drivers looked off-road slightly longer when ACC controlled headway. Higher levels of automation could further impact commercial driver visual behavior.